Brain and effort: brain activation and effort-related working memory in healthy participants and patients with working memory deficits - Engstrom, Maria; Landtblom, Anne-Marie; Karlsson, Thomas (Frontiers in Human Neuroscience, 2013)
Despite the interest in the neuroimaging of working memory, little is still known about the neurobiology of complex working memory in tasks that require simultaneous manipulation and storage of information. In addition to the central executive network, we assumed that the recently described salience network (involving the anterior insular cortex and the anterior cingulate cortex) might be of particular importance to working memory tasks that require complex, effortful processing. Method: Healthy participants (n=26) and participants suffering from working memory problems related to the Kleine-Levin syndrome (a specific form of periodic idiopathic hypersomnia; n=18) participated in the study. Participants were further divided into a high and low capacity group, according to performance on a working memory task (listening span). In a functional Magnetic Resonance Imaging (fMRI) study, participants were administered the reading span complex working memory task tapping cognitive effort. Principal findings: The fMRI-derived blood oxygen level dependent (BOLD) signal was modulated by 1) effort in both the central executive and the salience network and 2) capacity in the salience network in that high performers evidenced a weaker BOLD signal than low performers. In the salience network there was a dichotomy between the left and the right hemisphere; the right hemisphere elicited a steeper increase of the BOLD signal as a function of increasing effort. There was also a stronger functional connectivity within the central executive network because of increased task difficulty. Conclusion: The ability to allocate cognitive effort in complex working memory is contingent upon focused resources in the executive and in particular the salience network. Individual capacity during the complex working memory task is related to activity in the salience (but not the executive) network so that high-capacity participants evidence a lower signal and possibly hence a larger dynamic response.